Open data, big data: where do we go? - Ferrer-Sapena, Antonia; Sánchez-Pérez, Enrique A. (Anuario ThinkEPI, 2013)
The "open data" movement is becoming more popular in different contexts: public administration, science and companies; therefore, it is important to know its scope. The term has generated a lot of expectations related to transparency at all levels, data reuse and free access. This review discusses some of the expectations generated by this movement.
Keywords: Open data; Transparency; Public administration; Government.